La retroalimentación educativa y el desarrollo intelectual en los niños de la Institución Educativa Inicial N°602 San Juan Bautista 2022 - Chavez Cahuaza, Sila (2024)
The fundamental purpose of this study was to evaluate the correlation between the level of educational feedback and the level of intellectual development of children enrolled in the Institution Educative Initial N°602 San Juan Bautista 2022. To address this objective, a quantitative approach was adopted. relational nature, implementing a non-experimental, cross-sectional and correlational field research design. The population under study included all children enrolled in the aforementioned institution, and it was decided to select the total sample of the population, made up of 103 boys and girls, to carry out the research. The methodology used focused on observation, using a specific guide as an instrument for data collection, which was validated by experts in the field. The analysis of the association between the variables using Spearman's Rho correlation shows a coefficient of 0.784 between educational feedback and the intellectual development of the children of the Institution Educative Initial N°602 San Juan Bautista, with a significance level of 0.05. This coefficient indicates a strong positive relationship between both variables. The significant correlation suggests that as the level of educational feedback improves, the level of intellectual development of children improves.